No magic bullets: Insights on drivers of stunting decline from an analysis of subnational success cases in India - Avula, Rasmi; Nguyen, Phuong Hong; Kohli, Neha; Kanani, Shubhada; Menon, Purnima (American Society for Nutrition, 2020)
Global attention to reducing childhood stunting has increased the demand for guidance on translating policies into impact. Evidence from national-level success cases is emerging but little is known about how subnational entities can accelerate change. In India, despite a common national framework of programs/policies targeting many determinants of child growth, stunting reduction has varied across states. We aimed to understand drivers of change in stunting at state-level and to identify programmatic, social and political factors that contributed to these changes.